Abyssomicin derivatives from the rhizosphere soil actinomycete Microbispora rhizosphaerae sp. nov. TBRC6028. (May 2021) - Bunbamrung, Nantiya; Kittisrisopit, Suchada; Intaraudom, Chakapong; Dramae, Aibrohim; Thawai, Chitti; Niemhom, Nantawan; Harding, David J.; Auncharoen, Patchanee; Pittayakhajonwut, Pattama
Abstract: Three undescribed abyssomicin derivatives, including microbimisin, abyssomicins Z1, and Z2, were isolated from the soil actinomycete Microbispora rhizosphaerae sp. nov. TBRC6028. Chemical structures were determined by NMR spectroscopic data ( 1 H, 13 C, COSY, HSQC, HMBC, and NOESY spectra) and the absolute configurations were verified by single-crystal X-ray diffraction analyses together with the ECD spectral data. Microbimisin and abyssomicin Z1 exhibited weak antibacterial activity against Bacillus cereus with MIC values of 25.0 and 50.0 μg/mL without cytotoxicity against MCF-7 and Vero cells at the concentration of 50 μg/mL. Graphical abstract: Image 1 Highlights: Three undescribed abyssomicin derivatives were isolated from Microbispora rhizosphaerae sp. nov. TBRC6028. Chemical structures were determined by NMR spectroscopic information. Absolute configurations were assigned based on X-ray diffraction analyses and ECD spectra. The isolated compounds showed weak anti -Bacillus cereus activity.